The Australian bushfire disaster: How to avoid repeating this catastrophe for biodiversity. (3rd March 2021) - Celermajer, Danielle; Lyster, Rosemary; Wardle, Glenda M.; Walmsley, Rachel; Couzens, Ed
Abstract: Bushfires in Australia in the "Black Summer" of 2019–2020 shocked the world. Research is allowing us to begin to appreciate the scale of the catastrophe for humans, other animals, and the environment. If we are to anticipate, mitigate, and prevent further catastrophes and to protect biodiversity as best we can, we must develop a comprehensive picture of the impacts of these recent bushfires, understand their causes, and trace where responsibility for their catastrophic impact on biodiversity falls. This opinion piece argues that doing so requires an analysis that combines legal, philosophical, and scientific lenses. Correlatively, a comprehensive response demands the rapid introduction of a range of scientific, legal, political, economic, and cultural changes, not simply to reduce fossil fuel emissions and better protect biodiversity, but to disable the ideological conditions that enable the existing policy framework. This article is categorized under: Climate, Ecology, and Conservation > Conservation Strategies Abstract : An ecological approach to understanding the causes and effects of the Black Summer fires